Happy people read & drink coffee - Martin-Lugand, Agnès (Weinstein Books, 2016)
Diane is the owner of Happy People Read and Drink Coffee, a literary café in Paris. When her husband and daughter die in a car accident, her life is overturned and the world as she knows it instantly disappears. Trapped by her memories, she moves to a small town on the Irish coast. There she falls into a surprising and tumultuous romance with Edward, a taciturn photographer who lives next door.